(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: With the establishment of high-technology centers around the world, including in Vietnam, modern medical equipment and advanced imaging systems have been widely developed. Contrast agents are substances used in diagnostic imaging procedures such as CT and MRI to enhance visualization and improve diagnostic accuracy. Currently, co-ordinated contrast media are the most used because they are considered relatively safe compared with other types of contrast agents. Objective: To describe the indications, patient characteristics, and outcomes of patients undergoing contrast-enhanced computed tomography (CT), and to investigate some adverse reactions following contrast administration as well as several factors associated with the use of contrast media among patients at the Department of Diagnostic Imaging, National Hospital of Endocrinology in 2025. Methodology: A cross-sectional descriptive study combining qualitative and quantitative analyses to assess the service responsiveness of the Diagnostic Imaging Department at the National Hospital of Endocrinology. Results: The contrast Omnipaque 350 mg I/ml (Iohexol) was the most used (85%), followed by Ultravist 300 mg I/ml (Iopromide) (15%). The average administered dose ranged from 65–75 ml per examination. Comparison with the James formula, used to estimate the recommended dose based on body weight, showed that the actual administered dose was equivalent to the calculated dose and did not exceed the recommended limit, thereby ensuring safety and minimizing the risk of contrast-induced nephrotoxicity. Most patients tolerated the contrast media well, with only a small proportion experiencing adverse reactions after injection. Specifically, 68.7% of patients had no significant symptoms, apart from transient warmth; 22.1% experienced mild reactions such as a generalized warm sensation, nausea–vomiting, or a metallic taste in the mouth; and 1% developed moderate or severe reactions, including urticaria, itching, dyspnea, or mild hypotension. However, all reactions were promptly recognized and appropriately managed, and no severe complications or deaths were recorded. Patients with a history of drug allergies or underlying chronic diseases (such as diabetes mellitus, renal impairment, or hypertension) had a significantly higher incidence of adverse reactions compared with those without risk factors (p < 0.05). Meanwhile, factors such as sex, educational level, financial capacity, understanding of the imaging procedure, and length of hospital stay did not affect the use of contrast media among patients. Conclusion: The use of contrast media in computed tomography (CT) examinations at the Department of Diagnostic Imaging, National Hospital of Endocrinology was found to be within safe limits and ensured diagnostic effectiveness. Adverse reactions following contrast injection at the National Hospital of Endocrinology were mostly mild, occurred at a low frequency, and were well controlled in accordance with established procedures and international standards.